Analysis Of Heart Decrease In Hypertension Patients With Karotis Artery Massage - Asnidar; Tenriwati (Comprehensive Health Care, 2017)
Hypertension is a disease that causes a high morbidity rate. The purpose of this study was to analyze the decrease in heart rate of hypertensive patients before and after doing massage on the carotid artery at the Bontobangun Public Health Center. design with population and sample that is all hypertension patients in Public Health Center of Bonto Public Health Center as many as 30 people. The sampling technique used was accidentaly sampling. The results of this study were in the pre-test there were 17 people (56.7%) who were in the category of moderate heart rate, 13 people (43.3%) high heart rate, in the post-test there were 25 people (83.3%) who had moderate heart rate , and 5 people (16.7%) had high heart rates. The conclusion of this study is that there is a decrease in heart rate of hypertension patients after carotid artery massage in public polyclinic public clinics at Bonto Wake with a value of p = 0.008 <α = 0.05. suggestions from this study are so that the results of this study can add a reference regarding carotid artery massage to decrease heart rate in patients with hypertension in the general poly bontobangun puskesmas.